2011
DOI: 10.1038/icb.2011.9
|View full text |Cite
|
Sign up to set email alerts
|

IFN‐γ‐mediated efficacy of allergen‐free immunotherapy using mycobacterial antigens and CpG‐ODN

Abstract: Epidemiological and experimental evidence supports the notion that microbial infections that are known to induce Th1-type immune responses can suppress Th2 immune responses, which are characteristics of allergic disorders. However, live microbial immunization might not be feasible for human immunotherapy. Here, we evaluated whether induction of Th1 immunity by the immunostimulatory sequences of CpG-oligodeoxynucleotides (CpG-ODN), with or without culture filtrate proteins (CFP), from Mycobacterium tuberculosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 37 publications
(73 reference statements)
1
29
0
5
Order By: Relevance
“…A study has reported that the interaction between BCG and toll-like receptor (TLR) 2 on DCs may affect the differentiation of naïve T cell mainly to Th1-like cells with the help of IL-10, IL-12, and so forth 43. In addition, recently, some studies have reported that IFN-γ is essential to suppress allergic responses 44. It would be worth to perform the study of BCG-DCs on damping allergic inflammation in IFN-γ- or TLR2-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…A study has reported that the interaction between BCG and toll-like receptor (TLR) 2 on DCs may affect the differentiation of naïve T cell mainly to Th1-like cells with the help of IL-10, IL-12, and so forth 43. In addition, recently, some studies have reported that IFN-γ is essential to suppress allergic responses 44. It would be worth to perform the study of BCG-DCs on damping allergic inflammation in IFN-γ- or TLR2-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…The paper by Fonseca et al . (e‐pub ahead of print: Immunology and Cell Biology (15 March 2011); doi:10.1038/icb.2011.9) reports the effect of two microbial products on a mouse model of asthma 1 . The authors found that treatment with the combination of CpG‐oligodeoxynucloeotides (CpG) and mycobacterial proteins reduced inflammation and airway hyperresponsiveness.…”
mentioning
confidence: 99%
“…CpG and mycobacteria have separately been the subject of extensive research for their potential to inhibit allergic diseases, and both types of agent have been tested (separately) in clinical trials of immunotherapy. The paper by Fonseca et al is significant because it demonstrates improved efficacy when the two different agents are combined 1 …”
mentioning
confidence: 99%
See 2 more Smart Citations